Measuring circuits of two double electro-induction spherical sensors of electric field strength of closed type constructively united into a single whole - S. V. Biryukov; L. V. Tyukina; A. V. Tyukin (Омский научный вестник)
To control the levels of electric fields, electric field strength sensors are required. Currently, for these purposes, the most promising are dual electric induction sensors, which are a constructive combination of two double sensors into one whole. There are two types of dual sensors with overhead, composite and separate sensing elements. The output signals of such sensors are electrical parameters such as charge, current and voltage. Studies have shown that electrical charge has the greatest advantage. To remove the charge from the sensor, it is recommended to use a current integrator (charge amplifier) as the primary measuring circuit. Secondary measuring circuits of the dual sensors considered in this work are used for averaging the signals of double sensors in order to reduce the error from the inhomogeneity of the electric field and form an output signal proportional to the field strength. It has been established in the work that sensors with overhead and composite sensitive elements allow to perceive the intensity of an inhomogeneous electric field with an error not exceeding +4,6 % in the spatial measurement range 0a1. The work also determined the sensitivities of two types of dual sensors of the electric field strength.